2004
DOI: 10.1016/j.tet.2003.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Triruthenium dodecacarbonyl/triphenylphosphine catalyzed dehydrogenation of primary and secondary alcohols

Abstract: Dehydrogenation of alcohols into aldehydes and ketones by Ru 3 (CO) 12 /PPh 3 based homogeneous catalysis has been investigated as an alternative for the classical Oppenauer oxidation. Several catalytic systems have been screened in the Oppenauer-like oxidation of alcohols. A systematic study of various combinations of Ru 3 (CO) 12 , mono-and bidentate ligands and hydride acceptors was performed to enable dehydrogenation of primary alcohols to stop at the aldehyde stage. Among many H-acceptors screened, diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Conventional diol-alkyne transfer hydrogenation provides the initial quantities of dione required for entry into the catalytic cycle. 23,24,74 …”
Section: Conversion Of Secondary Alcohols To Tertiary Alcoholsmentioning
confidence: 99%
“…Conventional diol-alkyne transfer hydrogenation provides the initial quantities of dione required for entry into the catalytic cycle. 23,24,74 …”
Section: Conversion Of Secondary Alcohols To Tertiary Alcoholsmentioning
confidence: 99%
“…Ruthenium catalysts are known to oxidize alcohols and other substrates according to different reaction mechanisms such as hydridometal or oxometal pathways and even radical mechanism, depending on the oxidation states of ruthenium, oxidant and cocatalysts or additives [23][24][25][26][27][28][29][30][31][32][33][34][35]. Various homogeneous Ru catalysts, like RuCl 3 [36], perruthenate [37,38] or Ru complexes [20,39,40] preferentially with salen [41], amine [42][43][44]50] or phosphine [45][46][47][48][49][50][51] ligands, also in combination with bases and TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxyl) as cocatalyst were successfully employed in the aerobic oxidation. Bäckvall and co-workers [52] developed methods for the oxidation of alcohols via biomimetic multi-stage electron transfers.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional diol-alkyne transfer hydrogenation provides the initial quantities of dione required for entry into the catalytic cycle. 23,24,74 Intermolecular catalytic reductive couplings of α-olefins with unactivated aldehydes and ketones remains an unmet challenge. [75][76][77] In a significant step toward this goal, it was found that ruthenium(0) catalysts promote the transfer hydrogenative C-C coupling of 3-hydroxy-2-oxindoles with α-olefins, including feedstocks such as ethylene, propylene and styrene, to furnish the branched adducts as single regio-and diastereomers.…”
Section: Conversion Of Secondary Alcohols To Tertiary Alcoholsmentioning
confidence: 99%